Application of GIS and Remote Sensing Techniques for Hydromorphometric Analysis of Wadi Al-Mohammadi Basin, Western Iraq - Mahmood H. D. Al-Kubaisi,; Qusai Y. S. Al-Kubaisi, (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
Hydromorphometric analysis as a method is considered one of the most reliable and used methods in solving hydrological problems. Where it is possible to know the volume of runoff and the rest of the elements that enter into the water balance. Geographical Information System and Remote Sensing is the technique that used the hydro-morphometric analysis of the Wadi Al-Mohammadi basin. Wadi Al-Mohammadi, located in the Western Desert, is one of the main valleys that flow into the Euphrates River. It is considered an important basin, because of its many characteristics, including its relatively large area and the amount of water drained through, which is used mainly in watering livestock and agriculture, in addition to industrial purposes such as the production of washed sand, gravel that scattered on both sides of the valley. The hydrological analysis included several steps, which gave the results of the flow accumulation with the highest value in the lower part of the basin. The results represented by form characteristics confirm that the shape of the basin is far from the round shape, which reflects the basin’s characteristics with the regular surface flow in time and relatively low drainages. Wadi Al-Mohammadi basin has reached the 5th order to flow into the Euphrates River. It has two types of drainage patterns, the dendritic pattern, and the parallel pattern. Wadi Al-Mohammadi basin is categorized as extremely low drainage density, very low drainage frequency, very coarse drainage texture, lower infiltration number, and low relief slope. Based on the results, the basin is characterized by an almost flat plateau surface, with a gradual slope homogeneous and good permeable soil conditions, and in other parts influenced by the structural phenomena under the surface, the high permeability of sediments over which streams pass, higher the infiltration and lower runoff.